Analisis Kualitatif Model Timmons Dalam Pengelolaan Program Kewirausahaan Mahasiswa - Sella Anggelia Putri; Sumarno Sumarno; Brilliant Asmit (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2026)
University student entrepreneurship programs played a strategic role in developing entrepreneurial competencies and skills. However, effective management of these programs faced challenges in sustainably balancing opportunities, resources, and teams. This study aimed to optimize student entrepreneurship program management using the Timmons entrepreneurship model framework, which emphasized the interrelationship between opportunities, resources, and teams. A descriptive qualitative approach was employed, with data collected through in-depth interviews and documentation from student entrepreneurship teams, partners, and program managers. Data were analyzed using the interactive analysis model, consisting of data reduction, data presentation, and conclusion drawing with verification. Results showed that opportunity, resource, and team elements were applied and interrelated in program implementation. However, balance among these three elements remained suboptimal, indicating the need to strengthen entrepreneurship program managers' roles to enhance student entrepreneurship programs.